Methodological approaches and tools for assessing the innovative development of construction enterprises - Halunka, O.; Palahitskyi, V.; Kovtun, A. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to topical issues, models and methods of evaluating innovative processes in the field of construction. In the conditions of war, rapidly changing economic conditions and growing competition in the construction work market, innovation is a key factor contributing to the improvement of the efficiency of the companies in the construction sector of the economy. In the first part of the article, the authors consider the existing methods, approaches and models for evaluating the innovative development of enterprises in various sectors of the economy, focusing on their theoretical foundations and possibilities of application in the practice of the construction industry. The main criteria and indicators that allow for a comprehensive assessment of the level of innovativeness of enterprises are analyzed, including such aspects as financial resources, scientific developments, the introduction of new technologies and management methods, as well as integral indicators for evaluating all aspects of enterprise activity. Modern methods and means of evaluating innovative development are discussed, such as the analysis of key performance indicators and system coefficients, integral indicators, economic-mathematical modeling, as well as other methods of quantitative and qualitative evaluation. Special attention is paid to the implementation of digital technologies and tools (for example, project management systems, Big Data and analytics) that allow for more in-depth and objective analysis. The final part of the article summarizes and formulates recommendations for practitioners in the field of management of construction enterprises. The main directions for future research related to the development of new methods and approaches to the assessment of innovative development in the conditions of dynamic changes in the market are highlighted. Construction innovation has been identified as critical to addressing issues such as rising material costs, labor shortages, and environmental issues, so this direction includes the introduction of new technologies, materials, and processes to improve efficiency, reduce costs, and improve the quality of construction projects. By evaluating their innovation development, construction companies can identify strengths, weaknesses and opportunities that will allow them to remain competitive and meet future demands. Thus, the article is of interest to both scientists and practitioners who seek to adapt their business processes to modern conditions and increase their innovative activity.